PENGARUH INTENSITAS PENGGUNAAN TIKTOK TERHADAP SIKAP KEAGAMAAN MAHASISWA PAI UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Nurr, Amir (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
Abstract This study aims to determine the effect of the intensity of TikTok use on the religious attitudes of UMY PAI students of the 2021 batch. This type of research is field research, while the approach used is a quantitative approach with data collection techniques through questionnaires distributed to UMY PAI students of the 2021 batch. The analysis was carried out using a simple linear regression model. The results showed that the use of the TikTok application by students in consuming religious content was in the moderate category with an average score of 53.81. These results indicate that most students use the TikTok application neither too excessively nor too minimally. Meanwhile, the religious attitudes of PAI students of the 2021 batch were mostly in the good category, the average value of students' religious attitudes was 52.57. These results indicate that the majority of students have quite high religious attitudes, which are most likely influenced by factors such as social environment, spiritual experience, life needs, intellectual development, religious motivation and age. The results of the simple regression test showed that the intensity of TikTok application use had an influence of 32.7% on students' religious attitudes. This means that the more active students are in accessing and utilizing religious and positive content on TikTok, the more their religious attitudes will increase.